Generic and subgeneric status of aedine mosquito species (Diptera: Culicidae: Aedini) occurring in the Australasian Region - Reinert, John F.; Harbach, Ralph E. (Zootaxa, 2005)
Species of Aedini occurring in the Australasian Region are listed with their current generic-level assignments. The purpose of this list is to enable entomologists, public health personnel, and mosquito control workers to more quickly become familiar with recent formal taxonomic changes within the tribe.